Molecular dynamics simulation of the competitive adsorption behavior of effluent organic matters by heated aluminum oxide particles (HAOPs) - Ma, Yunqiao (2022)
Fouling mitigation of reverse osmosis membranes using various pre-treatment methods has received tremendous attention in the past years. The use of dynamic membranes particularly composed of heated aluminum oxide particles (HAOPs) appears to be a promising approach. Based off adsorption behaviors by individual foulants revealed by molecular dynamics (MD) simulations in an earlier study, this study targeted to understand the competitive adsorption of different constituents of effluent organic matters (EfOM) on HAOPs, which mimics the high local foulant concentration at the boundary layer. Quantitative analysis reveals that (i) EfOM constituents, except for low-molecular-weight neutrals, exhibit means to anchor onto HAOPs despite steric hindrance; (ii) adsorbed foulants exhibit significantly lower mobility and flexibility, indicating excellent adsorption capability of HAOPs before the dynamic membrane layer becoomes fully saturated with EfOM; and (iii) divalent ions and carboxylic group play critical roles in facilitating the adsorption of foulants. The MD results provide molecular-level mechanistic insights on the superior pre-treatment effectiveness by HAOPs.